PENERAPAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KERAGAMAN BUDAYA INDONESIAKU KELAS V SD NEGERI 2 MATA IE - Noralimah dabutar; Mislinawati; Nurmasyitah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This classroom action research was motivated by low student learning outcomes in "My Indonesian Cultural Diversity" due to teacher-centered, unvaried learning that lacked integration with students' real experiences. This study aims to determine the increase in teacher activity, student activity, and learning outcomes using the Culturally Responsive Teaching (CRT) approach. Employing a qualitative approach with the Kemmis and McTaggart Classroom Action Research (PTK) model, this study was conducted in two cycles. The subjects were 20 class VB students at SD Negeri 2 Mata Ie (12 female, 8 male). Data were collected via observations and learning tests, then analyzed using qualitative descriptive analysis. The results show that the CRT approach significantly improved all parameters. Teacher activity scores rose from 91 in cycle I to a perfect 100 in cycle II, maintaining a "very good" category. Student activity also increased substantially from 76 in cycle I to 96.2 in cycle II, matching the "very good" category. Furthermore, student learning outcomes enhanced remarkably; the class average increased from 75.2 with 70% classical completeness in cycle I to 89 with 100% classical completeness in cycle II. This progress occurs because learning is directly linked to cultural experiences and traditions close to students' daily lives, making the process more meaningful, active, and enjoyable. In conclusion, the application of the Culturally Responsive Teaching (CRT) approach is highly effective in increasing teacher activity, student activity, and student learning outcomes in class V of SD Negeri 2 Mata Ie. Keywords: Culturally Responsive Teaching (CRT), learning outcomes, Indonesian cultural diversity.